Platelet phagocytosis by neutrophils in a patient with antiphospholipid syndrome. Issue 1 (14th September 2021) - Zhang, Xiaoying; Li, Chun; Li, Zhanguo
Abstract : Platelet phagocytosis by neutrophils in a patient with antiphospholipid syndrome